From Tradition to Innovation: Inductive Approach in Developing Jurumiyah-Based Arabic Grammar Materials - Muhammad Bagus Aufus Shofi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to develop Arabic grammar teaching materials based on the Matan Jurumiyah textbook using an inductive approach, as well as to test their validity and effectiveness in improving students’ Arabic grammar skills. The method used is Research and Development (R&D) based on the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were first-grade students at the Madrasah Diniyah in the Hidayatul Qurro’ Islamic Boarding School in Blitar. Data were collected through observation, interviews, questionnaires, and tests (pretest and posttest), then analyzed using quantitative descriptive methods. The results showed that the developed teaching materials had a very high level of validity, with a score of 83% from media experts and 84% from content experts. Student responses to the teaching materials fell into the categories of “very interesting” and “highly needed.” Effectiveness testing showed a significant improvement in students’ grammar skills, as evidenced by an increase in the average score from 30.83 on the pretest to 80.83 on the posttest, with an N-gain value of 0.71, which falls into the moderate to high category. Thus, the Matan Jurumiyah-based Nahwu teaching materials using an inductive approach have been proven to be valid, engaging, and effective in improving students’ Arabic grammar skills, making them suitable for use in Nahwu instruction within Islamic boarding schools.